Design th!nking - Ambrose, Gavin; Harris, Paul (Basics design, 2010)
Offers an introduction to the process of generating creative ideas and concepts used by designers in order to start the process that leads to a finished piece of work. This title presents an approach to design as a problem-solving activity. It also features practical work examples and case studies